Pediatric kidney transplantation in China: an analysis from the IPNA Global Kidney Replacement Therapy Registry - Shen, Qian; Fang, Xiaoyan; Man, Xinyue; Zhai, Yihui; Liu, Longshan; Wang, Changxi; Shang, Wenjun; Feng, Guiwen; Zhang, Lei; Zeng, Li; Zhu, Youhua; Chen, Jing; et al. (Pediatric nephrology, 2021)
The International Pediatric Nephrology Association (IPNA) Global Kidney Replacement Therapy (KRT) Registry was established to evaluate the incidence and outcomes of kidney replacement therapy (dialysis and transplantation) provided to children worldwide. Analysis of registry data for separate regions is feasible.
Online publiziert: 15. September 2020
Gesehen am 29.09.2025